(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Management and excision of left hypochondriac mass of a 55 year old lady have been presented in the paper. The ultrasound of whole abdomen showed two big lumps in the left hypochondriac and lumbar region which after excision turned out to be a retroperitoneal schwannoma. The mass was removed by sacrificing the left kidney. Though it is a highly specialized operation and should be performed in a specialized center, sometimes general surgeons are unable to avoid the operation due to low economic condition of the patient. The case was performed at the Central Medical College Hospital, Comilla utilizing the existing facilities. Fortunately the patient is doing well and leading a normal life after one and half years of operation DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11420 J Bangladesh Coll Phys Surg 2012; 30: 105-107